2017
DOI: 10.1080/23337931.2017.1309658
|View full text |Cite|
|
Sign up to set email alerts
|

A novel etching technique for surface treatment of zirconia ceramics to improve adhesion of resin-based luting cements

Abstract: Objectives: Bonding of zirconia crowns and bridges to abutments is important, not only bonding of the thin resin layer to the abutment, but also bonding to the zirconia ceramic is crucial. Both mechanical and chemical adhesion are desired. Mechanical retention of dental porcelain achieved by etching with moderately concentrated hydrofluoric acid is not possible with zirconia ceramics.The purpose of this study was to show that etching is possible with relative low melting fluoride compounds such as ammonium hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 32 publications
5
38
0
4
Order By: Relevance
“…In addition, the XRD analysis results indicated that etching with KHF 2 and NH4HF2 chemically changed zirconia into fluoride compounds. Ruyter et al reported that these fluoride compounds as the etched surface product were assumed to be K 2(ZrF6) by fourier transform infrared absorption spectroscopic analysis 16) . These are results that dissolved zirconia and molted KHF2/NH4HF2 caused chemical reaction, resulting in sediments containing ZrF4 27) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the XRD analysis results indicated that etching with KHF 2 and NH4HF2 chemically changed zirconia into fluoride compounds. Ruyter et al reported that these fluoride compounds as the etched surface product were assumed to be K 2(ZrF6) by fourier transform infrared absorption spectroscopic analysis 16) . These are results that dissolved zirconia and molted KHF2/NH4HF2 caused chemical reaction, resulting in sediments containing ZrF4 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Current bonding protocols with light airborne particle abrasion (2.5 Bar, particle size 50 μ m) provide fairly good bond strength for resin‐bonded cantilevered fixed dental prostheses . Novel etching protocols are slowly developing and these could provide higher bond strength and enable use of zirconia in minimally invasive reconstructions in the future.…”
Section: Dental Ceramics As Adhesive Restorationsmentioning
confidence: 99%
“…For silica‐based ceramics, a pretreatment by hydrofluoric acid is recommended to form micro‐retentive surfaces . Alumina‐ and zirconia‐based ceramics resist hydrofluoric acid‐etching due to the absence of a silica phase . Therefore, airborne particle abrasion, laser irradiation, tribochemical silication, and coating with zirconia primer, singularly or in combination, have been suggested to increase the surface roughness of zirconia and thus the bonding strength.…”
mentioning
confidence: 99%
“…Casucci et al reported that the application of a selective infiltration etching procedure after air abrasion additionally improved the bond strength of zirconia. This prebonding treatment is based on the deflagration of low melting glass onto zirconia . The glass phase is consecutively partially dissolved by hydrofluoric acid to create a porous surface to improve bond strength to resin cement …”
mentioning
confidence: 99%